Hydro-priming as a Sustainable Approach for Improving Germination and Seedling Growth in Tomato (Solanum lycopersicum L.) - MK SUSHMA; SHIV K YADAV; S YADAV; R CHOUDHARY; A ANBALAGAN; K NAVYA; K KAUSHAL (Seed Research, 2026)
Uniform and rapid germination of seeds significantly impacts the yield and quality of tomato. Pre-sowing seed hydro-priming emerges as a cost-effective, and easily accessible technique for improving germination rates. Its affordability and effectiveness make it a preferred method for enhancing crop productivity. An experiment was conducted to assess the effect of different hydro-priming durations and seed to water ratio on germination and seedling growth of tomato. The treatments included hydro-priming of tomato seeds of the variety Pusa Rohini at different durations (3, 6, 9, 12, 15, 18, 21, 24, 27, 30, and 33 hours) with 1:1 and 1:2 (w/v) soaking volumes. The results of the study revealed that highest germination percentage (8.2%), shoot length (14.6%), root length (21.1%), total seedling length (19.5%), seedling fresh weight (43.3%), seedling dry weight (58.1%), seedling vigor index I (29.5%) and II (72.7%) were observed in 24 hours of priming duration compare to unprimed seeds. Similarly enhanced seed quality parameters were also observed in 1:2 (w/v) seed to water ratio. Thus, 24 hours of seed hydro-priming with 1:2 water ratio has been found to be effective in enhancing seed quality, including improvements in germination, seedling growth, and vigor in tomato.